(untitled) (Community Based Medical Journal, 2023)
The SARS-CoV-2 virus has been spreading rapidly within the range of infected patients, with an alarming fatality rate, so it has become a global pandemic and public health concern. As a result of this situation, an accelerated track for vaccine development has been set in motion. A vaccine, which is made from biological products, would be the ultimate weapon against the coronavirus and the best way to return to normal life. Several SARS-CoV-2 vaccine candidates have been identified in preclinical models and are currently being tested in clinical trials. SARS and the virus that causes Covid-19, SARS-CoV-2, are nearly identical, and both use spike proteins to bind to a specific receptor found on cells in human lungs. Based on previous involvement in the development of SARS-CoV vaccines, the SARS-CoV-2 immunization is currently being developed instantly in a variety of ways. Shortcuts in any of the steps of the research and development process can result in significant health hazards as well as a decrease in social confidence in the benefits of a vaccine. The purpose of this comprehensive review was to represent the developmental stages and challenges of various vaccine varieties used in the COVID-19 disorder. CBMJ 2023 January: Vol. 12 No. 01 P: 129-135